3D Printing in Surgical Management of Double Outlet Right Ventricle - Yoo, Shi-Joon; van Arsdell, Glen S. (Frontiers in Pediatrics, 2018)
Double outlet right ventricle is a heterogeneous group of congenital heart diseases that require individualized surgical approach based on precise understanding of the complex cardiovascular anatomy. Physical 3D print models not only allow fast and unequivocal perception of the complex anatomy but also eliminate misunderstanding or miscommunication among imagers and surgeons. Except for those cases showing well recognized classic surgical anatomy of DORV such as in cases with a typical subaortic or subpulmonary VSD, 3D print models are of enormous value in surgical decision and planning. Furthermore, 3D print models can also be used for rehearsal of the intended procedure before the actual surgery on the patient so that the outcome of the procedure is precisely predicted and the procedure can be optimally tailored for the patient’s specific anatomy. 3D print models are invaluable resource for hands-on surgical training of congenital heart surgeons.